Peptidases and neuropeptide processing - Smith, A. Ian (Methods in neurosciences ;, 1995)
The volumes in this series include contemporary techniques significant to a particular branch of neuroscience. They are an invaluable aid to the student as well as the experienced researcher not only in developing protocols in neuroscience but in disciplines where research is becoming closely related to neuroscience. Each volume of Methods in Neurosciences contains an index, and each chapter includes references. Dr. Conn became Editor-in-Chief of the series beginning with Volume 15, so each subsequent volume could be guest-edited by an expert in that specific field. This further strengthens the depth of coverage in Methods in Neurosciences for students and researchers alike. Comprehensive protocols included for: * Enzymes involved in the activation of bioactive peptidases and proteins * Prohormone/neuropeptide processing pathways * Enzymes involved in peptide metabolism * Posttranslational processing enzymes.